MEMORY AND NEGOTIATIONS OF IDENTITY IN TRAIN TO PAKISTAN - Giuseppe De Riso (Le Simplegadi, 2018)
This article focuses on Khushwant Singh’s Train to Pakistan to analyse the negotiations of identity among different ethnic communities at the time of the Partition between India and Pakistan which occurred in August 1947. In particular, this paper will try to show the impact, in the economy of social relationships and violence in Singh’s novel, of uncertainties put forward through the circulation of ‘rumours’ along and across the then still uncertain borders dividing the two budding nations.